دراسة تأثير الصنف والعروة الزراعية والتسميد على الصفات الإنتاجية لنبات الكراوية ( Carum carvi) - سليمان علي; المنصور براءة (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث خلال الموسم الزراعي 2010-2009 في محطة بحوث ستخيرس في اللاذقية التابعة للهيئة العامة للبحوث العلمية الزراعية بهدف دراسة تأثير الصنف , موعد الزراعة , التسميد على إنتاجية نبات الكراوية Carum carvi) ) تمت زراعة صنفي الكراوية (السوري والألماني ) في عروتين (خريفية , وربيعية ) , وتم إضافة السماد الكيميائي حسب المعادلة السمادية التقليدية (K:60 ,P:120, N:100) , على حين تم إضافة السماد العضوي بمعدل (20 طناً /هكتار) ,(30 طناً /هكتار) للمقارنة مع الشاهد بدون تسميد , وبواقع أربع مكررات لكل معاملة وفق تصميم التجارب العاملية ,حيث تم دراسة العديد من المؤشرات ومنها : نسبة الإنبات , وعدد الفروع, وعدد النورات الزهرية , ووزن الألف بذرة , والإنتاجية (كغ /هكتار). أشارت النتائج إلى وجود تباين معنوي بين الأصناف ومواعيد الزراعة ومعدلات التسميد , والتفاعل المتبادل بينها من حيث المؤشرات المدروسة . حيث وجد أن الصنف السوري تفوق في المؤشرات المدروسة على الصنف الألماني , وكان متوسط إنتاجه من البذور 1069.1)كغ/هكتار) بالمقارنة مع إنتاجية الصنف الألماني (796.6 كغ /ﻫكتار) كما أظهرت جميع معاملات التسميد تفوقاً معنوياً على الشاهد , على حين أظهر التسميد العضوي بجرعتيه المدروستين تفوقاً معنوياً على التسميد الكيميائي , فكان متوسط الإنتاج في التسميد الكيميائي (913كغ/هكتار)على حين بلغ المتوسط في التسميد العضوي بمعدل 20 طن/ ﻫ و30 طن /ﻫ( 955.2 كغ/ﻫ) , 1072.7) كغ /ﻫ) على التوالي. دلت النتائج إلى تفوق العروة الخريفية على الربيعية في جميع الصفات المدروسة حيث وصل متوسط الإنتاج في العروة الخريفية إلى ( 1136.55كغ/ﻫ ) بالمقارنة مع العروة الربيعية ( 729.25 كغ/ﻫ ) عموماً , كانت إنتاجية نبات الكراوية أعلى معنوياً في الصنف السوري المزروع في العروة الخريفية عند معاملة التسميد العضوي (30 طن /هكتار) . This research was carried out during 2009-2010 at the Experimental Farm Station (Stkhirs) in Lattakia, which belongs to GCSAR. The aim was to study the influence of variety, sowing date, and fertilization on the yield of Caraway plant ( Carum carvi L). The two varieties of Caraway seeds were sowed at two seasons (Autumn, Spring), and chemical fertilization was added according to usual treatment (N100 kg/h,P120 kg/h , K 60 kg/h), while organic fertilization was added at two levels (20 ton/h,30to / h) in order to compare them with the control without fertilization, with four replicates by the factorial experimental design. Many parameters were studied: germination percentage, number of brunches, number of umbels , the weight of (1000) seeds, and seed yield (kg/h). Results showed that there were significant differences among varieties, sowing, dates and fertilization rates and the interaction between them in terms of studied parameters. It was found that the Syrian variety was superior to the German one regarding the studied parameter, and the mean of its seed yield was (1069.1 kg/h) compared with (796.7kg/h) which belongs to German variety. All fertilization treatment showed significant superiority to the control, while the organic fertilization at two level showed significant superiority to the chemical treatment, and also showed that the mean of the seed yield at chemical fertilization was (913 kg/h), while at organic one in the level (20 ton/h,30to / h ) reaching (995.2kg/h and (1072.7kg/h) respectively. The results showed that sowing caraway seed in Autumn season on the basis of over all performance was significantly superior to Spring season, and that the mean of its seed yield reached (1136.55kg/ h ) while it was ( 729.25kg/h ) in Spring season. Generally, the best results regarding to the seed yield was the Syrian variety which sowed in the Autumn season at the level of (30 ton /h) of organic fertilization